Fabrication of low loss optical waveguides with a novel thermo-optical polymer material - Zhou, J.; Wong, W.H.; Pun, E.Y.B.; Shen, Y.Q.; Zhao, Y.X. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
The newly synthesized polymer, bisphenol A-aldehyde resin (BPA-resin) has many unique thermo-optical characteristics. The polymer has high transparency, relatively high refractive index, low birefringence, and large thermo-optics coefficient at the optical telecommunication wavelengths. Also, the single-mode channel waveguides have been fabricated using BPA-resin polymer. The experimental results show, that the polymer waveguide has a low propagation loss of 0.43 and 0.51 dB/cm at a wavelength of 1.31 and 1.55 mm, respectively, for both TE and TM polarizations. The low polarization dependence loss (PDL) of the waveguide was less than 0.1 dB/cm at above wavelengths, which can be applied in thermal-optical tuned devices.
Optica Applicata, Vol. 36, 2006, nr 2-3, s. 429-435
Keywords: optyka; polymeric optical waveguide; thermo-optical polymer; polarization dependence loss; optical telecommunication